The Influence of Product Quality, Trust, and Personal Selling on Customer Satisfaction in Using Products at Pegadaian Syariah Palu Plaza - Nurwahyuni; Syaifullah; Fatma; Ibah Misbah; Muhammad Syahril Moharom (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
This study aims to analyze the influence of product quality, trust, and personal selling on customer satisfaction at Pegadaian Syariah Palu Plaza. This study is motivated by the importance of understanding the factors that shape customer satisfaction amidst increasingly fierce competition among Islamic financial institutions. The research method used is quantitative with an associative approach. The study population includes all customers of Pegadaian Syariah Palu Plaza in 2023–2025 with a sample of 100 respondents selected through accidental sampling technique. Data were collected through questionnaires that have been tested for validity and reliability, then analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that product quality, trust, and personal selling have a positive and significant effect on customer satisfaction, both partially and simultaneously, with an R² value of 0.661, indicating that 66.1% of the variation in customer satisfaction is explained by these three variables, while the remainder is influenced by other factors outside this study. Theoretically, these results reinforce service marketing studies that customer satisfaction is a combination of good product quality, built trust, and effective personal selling. Practically, these findings provide a basis for Pegadaian Syariah Palu Plaza to improve service quality, build trust through transparency, and optimize personal selling communication strategies to increase customer loyalty and satisfaction.